ISRAEL BARU (Interpretasi Kritis atas Teologi Paulus tentang Israel di dalam Roma 9:6-8 dan 11:23-24) - Roy Charly H. P. Sipahutar (Jurnal Teologi Cultivation, 2019)
AbstractThis paper is an attempt to critically interpret the text of Romans 9: 6-8 and 11:23-24 which was born because of Paul's struggle with what happened in the Christian community of Rome. Israel is God's covenant people, but on the other hand they have also expressed rejection of the salvation brought by Jesus Christ. The status of the covenant people is being questioned by non-Jews, is it still valid? Paul explained that "God's Word cannot fail," meaning that Israel's status as a chosen people does not fade away. But Israel's refusal at the same time gave space to other nations to be part of that publicity. God who chooses a nation, God also allows the transplanting of other nations to be part of His people.Key Words: Israel, New Israel, Christianity, Romans 9: 6-8 and 11: 23-24